2018
DOI: 10.1186/s40594-018-0131-6
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ roles and identities in student-centered classrooms

Abstract: BackgroundStudents and teachers in twenty-first century STEM classrooms face significant challenges in preparing for post-secondary education, career, and citizenship. Educators have advocated for student-centered instruction as a way to face these challenges, with multiple programs emerging to shape and define such contexts. However, the ways to support teachers as they transition into non-traditional teaching must be developed. The purpose of this study is to explore the impacts on educators of teaching in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
155
1
20

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(249 citation statements)
references
References 40 publications
7
155
1
20
Order By: Relevance
“…The participation of lecturers in a discussion can motivate the students to be active so that students can use Padlet more optimally. This review reinforces the research by Whitton, which identifies that teacher involvement is very instrumental in the success of a class (Whitton, 2009) and because the participating teachers recognized multiple benefits in a student-centered classroom and differences from traditional classrooms (Keiler, 2018).…”
Section: Discussionsupporting
confidence: 75%
“…The participation of lecturers in a discussion can motivate the students to be active so that students can use Padlet more optimally. This review reinforces the research by Whitton, which identifies that teacher involvement is very instrumental in the success of a class (Whitton, 2009) and because the participating teachers recognized multiple benefits in a student-centered classroom and differences from traditional classrooms (Keiler, 2018).…”
Section: Discussionsupporting
confidence: 75%
“…In Keiler's (2018) study of teachers' identities, results revealed that participants' identities were closely connected to their instructional practices. In this study, participants learned to implement a new instructional model and through this process some participants transitioned easily to the new student-centered instructional model because of their identities and beliefs and some participants needed to make shifts in their identities and beliefs in order to comfortably implement this model.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Kecenderungan proses pembelajaran yang berpusat pada siswa dipengaruhi oleh tugas -tugas yang disusun oleh guru dan kemampuan guru dalam memberikan antisipasi respon terhadap respon yang diberikan oleh siswa. Berbagai instuksi yang merangsang siswa untuk mengkonstruksi ide dan intruksi berbasis penyelidikan yang diberikan oleh guru merupakan hal yang menciptakan proses pembelajaran yang berpusat pada siswa (Keiler, 2018). Siswa cenderung merespon secara positif terhadap perubahan-perubahan yang ada selama proses pembelajaran dan para guru menganggap diri mereka berhasil dalam upaya untuk menciptakan proses pembelajaran yang lebih berpusat pada siswa dengan variasi tugas -tugas yang telah disusun (Brown Wright, 2011).…”
Section: Gambar 3 Grafik Kecenderungan Aktivitas Siswa Dan Guru Dalaunclassified